MIR talks to Vinita Bali, Managing Director and CEO of Britannia Industries - REDDY, Srinivas K. (Institutional Knowledge at Singapore Management University, 2010)
Today we live in a truly global economy, no matter whether we talk about goods, services or manpower. Whereas economic growth rates in Europe and North America remain moderate, many Asian countries are booming despite last year´s economic downturn. This is reason enough for MIR to take a closer look at one of the rising stars: India. In June 2010, MIR talked to Vinita Bali, one of the few female CEOs of leading companies, who has worked in influential marketing positions on five continents. In describing how Britannia, one of the most famous Indian brands, handles everyday business and marketing challenges, she delivers a bright picture of the Indian economic situation.